Learning science locally: Community gardens and our future - Lloyd, David; Paige, Kathryn (Frontiers in Education, 2022)
The wholistic nature of gardening is an approach to learning that provides opportunities to place science education in a context that also values other ways of knowing and draws on the cognitive, the affective and the spiritual – knowing, feeling, connecting. This paper offers a case study of teaching gardening to primary students at The Old School Community Garden, in the Adelaide Hills, South Australia. As experienced science educators, we find that engaging young people in gardening provides them with the opportunity to see the world as a whole, learn science concepts while also addressing local issues such as organic food production. Our focus in this project is the use of the garden as a learning place for Year 1 students (aged 6-7) working with Year 4 students (aged 9-10). We also argue that nature teaching is part of the answer to liveable futures in this time of climate change, pandemics, and the possible crossing of other Earth boundaries. These challenges require educators to focus on futures thinking and transdisciplinary approaches in order to develop the dispositions needed to live in the present with a well-formed idea of where we want to go. Learning the science of gardening is clearly a central aspect – soil science, biological science, ecosystem management and a sustainable food supply.